Fenomena Buzzer Dalam Kontroversi Omnibus Law Di Media Sosial - Ain, Afifah Qurotul; Mirza, Khaidar; Caniago, Muhammad Fajar; Faturohman, Muhamad Heru (ijd-demos, 2021)
AbstractIn modern times like today, the development of information and communication technology is very rapid and cannot be stopped. Without realizing it, this technological development brings changes to human social behavior, technology offers new ways for humans to communicate through various new media (New Media). One of the New Media that is a product of technological developments that greatly affect our daily lives is social media. As time goes by, social media is not only a medium of communication or just spending free time. More than that, social media now has several other roles, one of which is as a means of conveying criticism of the situation created under a state government agency as well as a means of political campaigns for representation from the state government. With the formation of new behaviors in conveying voices in public spaces, many new things are also born, one of which is the buzzer phenomenon. Bauzzer on social media is associated with a party related to increasing trends and discussions on social media, it can be said that the buzzer is a raiser of issues or discussions about something on social media. On this occasion, the researcher will discuss the buzzer phenomenon on the controversial issue of undang-undang cipta kerja or omnibus lawKeywords: social media, buzzer, omnibus law, digital activism. AbstrakPada masa modern seperti sekarang ini, perkembangan teknologi informasi dan komunikasi sangatlah pesat dan tidak bisa di hentikan. Tanpa disadari, perkembangan teknologi ini membawa perubahan pada perilaku sosial manusia, teknologi menawarkan cara baru kepada manusia dalam berkomunikasi melalui berbagai media baru (New Media). Salah satu New Media yang menjadi produk perkembangan teknologi yang sangat berpengaruh pada kehidupan kita sehari-hari adalah media sosial. Seiring berjalannya waktu media sosial tidak hanya sebagai media komunikasi ataupun sekedar menghabiskan waktu luang. Lebih dari itu, media sosial kini telah memiliki beberapa peran lain salah satunya sebagai sarana penyampaian kritik atas situasi yang tercipta dibawah sebuah pemerintahan lembaga negara maupun sarana kampanye politik bagi representasi dari pemerintahan negara. Dengan terbentuknya perilaku baru dalam manyampaikan suara pada ruang publik, banyak hal baru pun ikut terlahir, salah satunya adalah fenomena buzzer. Bauzzer di sosial media di kaitkan dengan suatu pihak yang terkait dengan peningkatan trend dan bahasan di sosial media, bisa dikatakan bahwa buzzer merupakan pengangkat isu-isu atau pembahasan mengenai sesuatu di sosial media. Pada kesempatan kali ini peneliti akan membahas mengenai fenomena buzzer pada isu kontroversional UU cipta kerja atau omnibus lawKatakunci: media sosial, buzzer, omnibus law, aktivisme digital.